Caso: MSA del Perú - Cuba Cruz, Andrés Aarón (2018)
The present research work is based on a personal experience, having worked in the MSA company (August 2016 - May 2018), as a Sales Analyst. This position allowed me to go deeper into the company’s own activities, particularly in the procedures used for sales management. Within this context, and after having made the strategic marketing diagnosis, the sales management and the analysis of results, it was determined that said processes could be optimized, in order to significantly improve sales, promotion and distribution of their products in Peru. MSA (Mine Safety Appliances) is a multinational company created in 1914, dedicated to the manufacture and supply of industrial safety products and equipment, as well as products for personal protection, to protect users from risk or dangerous situations, being a world leader in this area. Its subsidiary in Peru, MSA del Perú S.A.C., has more than 100 employees and generates sales of more than $ 35 million dollars a year, being the company with the largest market share in the industrial security market in Peru. The problem addressed in this work lies in the current sales management of MSA del Perú S.A.C., which is done through distributors, using a classic model of the last century, based on the trilogy Manufacturer - Industrial Distributor - Final Client. This implies that the burden falls on the producer, that is, on MSA; who should seek to build loyalty to the process and its commercial partners. In order to be able to retain business partners and push the brand in the market, a system was implemented in which a commercial advisor would visit the main distributors in order to give them support regarding sales management, while also helping them with technical queries of the products offered by the brand. Thanks to this, sales increased by 30% compared to the previous year and it was concluded that said strategy should be implemented more frequently and they should apply it with other business partners.